Anticancer effect of petroleum ether extract from Bidens pilosa L and its constituent's analysis by GC-MS. (10th May 2018) - Shen, Yiwei; Sun, Zhouliang; Shi, Peiying; Wang, Gang; Wu, Youjia; Li, Shaoguang; Zheng, Yanjie; Huang, Liying; Lin, Liqing; Lin, Xinhua; Yao, Hong
Abstract: Ethnopharmacological relevance: Bidens pilosa L, belonging to the family of Acanthaceae, has been used as an anticancer medicine in folk in China. In our preliminary experiments, the petroleum ether extract from B. pilosa showed good cytotoxic activity to human lung cancer A549 cell. However, to date, it's lack of the further study on antitumor effect, mechanism and active substances composition of the petroleum ether extract of B. pilosa . Aim of the study: The study aimed to evaluate the anti-lung cancer efficacy of the petroleum ether extract from B. pilosa (PEEBP) in vitro and in vivo, explore the possible anticancer mechanisms, and further disclose the chemical composition of the extract. Materials and methods: B. pilosa was extracted with 75% ethanol (v/v), followed by extracted with petroleum ether to obtain the objective fraction. Antiproliferation effect of the petroleum ether extract in HepG2, A549, CNE and B16 cells was evaluated by MTT assay. The in vivo anticancer effect was examined by A549 cells nude mice xenograft tumor model. The possible effect mechanism was studied by western blot assay. The chemical constituents of the extract was analyzed by GC-MS. Results: The petroleum ether extract showed favorable antiproliferation activity against the four human cancer cell lines, especially for A549 cells with an IC50 of 49.11 ± 2.72 μg/mL. The extract inhibited the growth of A549 cell in mice with the inhibitory rates of 24.76%, 35.85% and 53.07% for 90, 180 and 360 mg/kg oral dosages, respectively. The B. pilosa extract could significantly down-regulate the expression of apoptosis-related protein Bcl-2 and up-regulate the protein expression of Bax and Caspase-3. 138 compounds were identified by GC-MS in the extract and the main chemical components were triterpenes, including 4, 22-cholestadien-3-one (4.82%), stigmasterol (4.56%), friedelan-3-one (3.28%), etc . Conclusion: The PEEBP is abundant of triterpenes and has significant anti-tumor activities against human A549 cells in vitro and in vivo, indicating it a potential anticancer agent. Graphical abstract: